2022
DOI: 10.1007/s12144-021-02629-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of cognitive appraisals in parental burnout: a preliminary analysis during the COVID-19 quarantine

Abstract: Counter-intuitively, sociodemographic characteristics account for a small proportion of explained variance in parental burnout. The present study conducted during the Covid-19 pandemic asks whether (i) sociodemographic characteristics are more predictive of parental burnout than usual in a situation of lockdown, (ii) situational factors, that is, the specific restrictive living conditions inherent in the context of lockdown, predict parental burnout better than sociodemographic characteristics do, and (iii) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
2
8
1
Order By: Relevance
“…The 6% of the parents who met the cutoff in this sample is within the 5–20% range reported in pre-pandemic studies ( Roskam et al., 2018 ; Séjourné et al, 2018 ). Our finding is also consistent with other studies reporting similar or lower levels of burnout among parents during COVID-19 ( Bastiaansen et al, 2021 ; Le Vigouroux et al, 2022b ; Swit & Breen, 2022 ; Woine et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The 6% of the parents who met the cutoff in this sample is within the 5–20% range reported in pre-pandemic studies ( Roskam et al., 2018 ; Séjourné et al, 2018 ). Our finding is also consistent with other studies reporting similar or lower levels of burnout among parents during COVID-19 ( Bastiaansen et al, 2021 ; Le Vigouroux et al, 2022b ; Swit & Breen, 2022 ; Woine et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…It is important to note that parental age was negatively associated with parental burnout in this sample during the second year of the COVID-19 pandemic. This finding is consistent with those from studies of parenting in the early stages of the pandemic ( Skjerdingstad et al, 2021 ; Sorkkila & Aunola, 2021 ; Woine et al, 2022 ). It could be that older age as a parent offered certain protective factors, such as increased parenting experience ( Woine et al, 2022 ), that helped parents cope with parenting stressors as pandemic-related changes continued into the second year.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Teacher burnout is also the focus of an increasing number of studies [18][19][20][21]. Additionally, working parents may experience high levels of stress in the home environment during the COVID-19 pandemic, leading to parental burnout [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…These findings might suggest that the measurement of these latter antecedents is more subject to parents' subjective perception than the measurement of the former (i.e., sociodemographic characteristics such as the number and age of the children, for example). A preliminary study conducted during the Covid-19 global pandemic (Woine et al, 2022) further showed that only 2 items intended to assess parents' subjective perception of their parenting situation during the pandemic (i.e., positive appraisal [When you think of the coronavirus health crisis, to what extent do you think it has had a positive impact on your parenthood and on your attitudes towards your children (e.g., experiencing more quality time, having closer contact)] and negative appraisal [When you think of the coronavirus health crisis, to what extent do you think it has had a negative impact on your parenthood and on your attitudes towards your children (e.g., experiencing less quality time, having more conflicts)]) predicted parental burnout much better than the 18 items which assessed the parents' objective sociodemographic/situational characteristics (e.g., age and gender of the parent, how many kids they had, whether they had to homeschool their children, whether they had a garden or a place where children could play outside the house, etc.). These findings offer an additional bundle of empirical evidence that cognitive appraisals may be operative in parental burnout.…”
Section: Introductionmentioning
confidence: 99%